Quality Education Sustainable Development (SDG-4) 2025: A Comparative Study of Government and Punjab Education Foundation Secondary Schools - Sabir Hussain; Masood Ahmad; Sobia Altaf; Muhammad Farooq Ahmad (PJE, 2024)
Quality of education is essential for the development of a nation, it is more important at the secondary school level because this level provides a nursery for higher education. The current study aimed to compare the government and Punjab Education Foundation Secondary Schools regarding quality education to meet sustainable development goal 4. Through simple random sampling technique, 108 teachers were selected from the government and 108 from Punjab Education Foundation secondary schools. Data were collected through a 5-point Likert scale on quality standards including: quality of management, teaching, infrastructure, school climate, and co-curricular activities. Independent sample t-tests were used to check the difference between both types of school systems. Government secondary schools were found to be better and follow maximum quality standards as compared to Punjab Education Foundation schools. It is suggested that Punjab Education Foundation Secondary Schools should follow the minimum quality standard set by the Punjab school minister to fulfill the vision of Goal No. 4 of Sustainable Development (SDG- 4) 2025 and enhance the quality of management, teachers, infrastructure, school climate, and co-curricular activities.